(untitled) (Jurnal Manajemen dan Kewirausahaan, 2007)
The purpose of this study ws to exmine direct and indirect effects of a integrated multidimensional model of transformational leadership upon organizational citizenship behaviour (OCBs) and considered quality of work life and organizational commitment as key antecedents. Participants comprised 190 teachers from ten middle school%2C whom completed a questionnaire. In this study%2C transformational ledership as an important correlate to the organizational citizenship behaviour that the link would be quality of work life%2C while the organizational commitment was unrelated. Wheb quality of work life middle school teachers superiors with transformational ledership behaviour of principals were likely to be related to greater organizational citizenship behaviour. Abstract in Bahasa Indonesia : Tujuan penelitian ini adalah untuk menguji hubungan langsung maupun tidak langsung dari sebuah model multidimensional mengenai pengaruh kepemimpinan transformasional terhadap perilaku ekstra peran yang dimediasi oleh kepuasan akan kualitas kehidupan kerja dan komitmen organisasional sebagai variabel antasenden. Sampel adalah 190 Guru Sekolah Menegah Umum (secara lengkap mengisi kuisioner). Dalam penelitian ini%2C secara signifikan kepuasan akan kualitas kehidupan kerja memediasi kepemimpinan transformasional terhadap perilaku ekstra peran%2C sebaliknya komitmen organisasional ditemukan tidak signifikan. Penerapan kepemimpinan transformasional dari kepala sekolah meningkatkan kepuasan akan kualitas kehidupan kerja%2C dan hal ini cenderung akan meningkatakan perilaku ekstra peran dari para guru. ransformational leadership%2C organizational citizenship behavior%2C quality of work life%2C and commitment organizational.